Assessment of end user traits and physicochemical qualities of cassava flour: a case of Zombo district, Uganda - Nanyonjo, Ann Ritah; Kawuki, Robert Sezi; Wembabazi, Enoch; Hale, Tufan (International Journal of Food Science and Technology, 2021)
Cassava breeding programmes in Uganda do not currently select materials based on flour making quality, explaining in part the low adoption rates of many released varieties. In this study, we describe end user trait preferences, processing qualities and physicochemical properties of cassava flour. We found that higher proportion of women than men showed preference for most attributes of cassava flour quality evaluated in this study. Preference for colour was 66% and 52% among women and men, respectively, while that for stickiness of Kwon was 26% (women) and 15% (men). Ease of peeling and stickiness of Kwon were key processing traits. Heap fermented flour had higher pasting temperatures, but lower viscosities than sun-dried flour, and had lower amylose content compared to fresh root starch. The results demonstrate the importance of gender sensitive participatory evaluation of breeding materials, in tandem with physicochemical evaluation during selection of best possible candidate breeding lines.